THE CHALLENGE OF ASEAN MIGRANT WORKERS’ WELFARE COMMODITAZION VERSUS HUMAN RIGHTS? - Sinta , Herindrasti (Mandala: Jurnal Ilmu Hubungan Internasional, 2018)
Critical attention toward migrant worker issues in the regional level grows in accordance with the universalization of human rights principle. There is no exception in Southeast Asia, where the level of interstate labour migration shows an increasing trend. Cases of exploitation and violence on migrant workers in recipient countries clearly indicate the existence of basic “humanity threat”, which intimidate migrant workers, on social, economic and political structures. Legal protection initiatives have been conducted by international regimes, especially through the Convention on the Protection of the Rights of all Migrant Workers and Members of their Families (1990). However, in ASEAN level, strong interests from each state member has caused difficulties in the ratification of the ASEAN Instrument of the Protection of the Rights of Migrant Workers. Why do most ASEAN countries refuse to ratify the instrument? What is the role of ASEAN in this initiative? This paper examines how far ASEAN countries will protect their workers, which further test their commitment on ASEAN Social Cultural Community 2025’s goal of increasing the quality of people’s life through people-centred and people-oriented cooperation. This paper applies qualitative approach with descriptive analysis method by exploring and understanding the meaning of primary and secondary data. This paper further argues that national interests of recipient countries are the main factor in preventing the ratification of the Instrument of the Protection of the Rights of Migrant Workers in ASEAN. Initiator nations like Indonesia and the Philippines must keep trying to approach other ASEAN state members to encourage creating National Law and standardizing the National Policy for migrant workers as one centralized Customary Law through the Regional Agreement. Centralization will ensure that protection to all migrant workers can be shouldered through risk-sharing practice by all ASEAN state members.